Enhanced gas separation performance using carbon membranes containing nanocrystalline cellulose and BTDA-TDI/MDI polyimide - Sazali, Norazlianie (Elsevier B.V., 2018)
This paper presents the derivation of carbon membranes from BTDA-TDI/MDI polyimide (PI) prepared via a dip-coating technique on an inorganic tubular support surface, followed by a heat treatment (stabilization and carbonization) under N2 gas flow. In order to enhance the gas separation performance of the resultant carbon membrane, a synthesized nanocrystalline cellulose (NCC) using tissue paper as an additive was added into the dope solution at various carbonization temperatures of 600, 700, 800, and 900 °C. The NCC was prepared by extracting the unprinted area of a newspaper and was processed as an additive in the polymer solution. The chemical structure, morphological structure, and gas permeation properties of the resultant membrane were analyzed. Special attention was given to the physicochemical characteristics of the resulting PI/NCC-based carbon membrane and its corresponding gas permeation properties. Pure gas permeation tests were performed using CO2, CH4, O2, and N2 at room temperature. The gas permeation data demonstrated that the carbon membrane exhibited an excellent performance compared to the polymeric membrane. Enhancement in both gas permeance and selectivity were observed in the NCC-containing carbon membranes prepared at carbonization temperature of 800 °C, with the CO2/CH4 selectivity of 68.2 ± 3.3, the CO2/N2 selectivity of 66.3 ± 2.2, and the O2/N2 selectivity of 9.3 ± 2.5, with respect to the neat carbon membrane. By manipulating various carbonization temperatures, carbon membranes with different structures and properties were obtained.